Principi della didattica di Mies nei progetti di Brenner, Jansone e Lippert per un museo d’arte - Rosellini, Anna (Opus Incertum, 2023)
When Mies began teaching at the Armour Institute, he defined a programme that would make technical and industrial developments in the United States problematic and theoretical. Some of the exercises concerned the relationship between painting, sculpture and architecture, and were transformed into museum projects. In the paper, the projects for exhibition spaces drawn up by Brenner, Jansone and Lippert for the Master of Science in Architecture are analysed from archive documents. The spatial, structural and material characteristics of these projects are reconstructed, as are their relationships to the programmes of the Department of Architecture, the design processes suggested by Mies, Le Corbusier’s projects for museums, and the Museum for a Small City designed by Mies together with Danforth. The theses of Brenner, Jansone and Lippert, united by the choice of a museum system that transfigured Le Corbusier’s model in the light of Mies’s vision, appear to be decisive documents not only for understanding the Department of Architecture’s didactic orientations, but also for accessing Mies’s unspeakable art of tracing and arranging lines and planes in space.